Evaluation of alginate dialdehyde as a suitable crosslinker on modifying porcine acellular dermal matrix: The aggregation of collagenous fibers. Issue 25 (22nd March 2016) - Zhu, Shichen; Gu, Zhipeng; Hu, Yang; Dan, Weihua; Xiong, Shanbai
ABSTRACT: Porcine acellular dermal matrix (PADM) has been investigated widely as a natural biomaterial. However, the success of PADM has been limited by insufficient stability and poor physicochemical properties. In our work, alginate dialdehyde (ADA) with various oxidation degrees (OD = 25%, 45%, and 65%) were explored to modify PADM, while glutaraldehyde (GA), dehydrathermal treatment (DHT), and carbodiimide (EDC) were used as the control. The efficacy of ADA on modifying PADM increased along with the rising of oxidation degree. The ADA (OD = 65% and 45%) groups showed better mechanical and thermal stability, crosslink density, and resistance to enzymatic degradation than ADA (OD = 25%) and DHT + EDC group. Meanwhile, the structure of PADM crosslinked by ADA (OD = 45% and 65%) were maintained largely. Further, ADA (OD = 45%) group revealed better cytocompatibility than DHT + EDC, ADA (OD = 65%) and GA group. Considering the balance of cytocompatibility and physicochemical behavior, ADA (OD = 45%) was more suitable as a natural derived crosslinker to modify PADM in tissue engineering. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43550. Abstract :